Membuat Media Pembelajaran Pembuatan Blog Berbasis Multimedia Pada SMK Negeri 1 Gondang Sragen - Tri Anasari - Universitas Surakarta (SPEED - Sentra Penelitian Engineering dan Edukasi, 2008)
ABSTRACT : With the rapid development of technology that can be utilized to facilitate thelearning process. Learning Media is one of the product development of technology that has provencapable of creating new solutions for independent learning process.At present almost all the people who often had the Internet already has a blog. In theInternet world, everyone wants to be able to actualize himself known to people, so it can be seenby the public, like a diary which is always uptodate all the time posted on a web page. So it takes aweb-based Content Management System (CMS) to facilitate this web owners in managing thecontent on the web. One posting on the web application is to use wordpress, because it is opensource, supported by attractive features and facilities as well as full support from forums anddeveloper community.Formulation of the problem of this research is to study creating a blog with the conventionalway of reading, listening, understanding and practice is considered less effective and efficient aswell as how to conduct interactive learning media wordpress using a multimedia computer. Thepurposes of this study was to availability of multimedia-based instructional media wordpress.The research method is a method of data collection are observation, Bibliography,Interviews, Analysis and System Design, System Testing and Implementation System. After goingthrough several stages in the manufacture of this wordpress tutorial it can be concluded with thelearning-making learning media blogs more easily learned by students as well as instructionalmedia in the form of a CD and performed by playing a CD of learning in a multimedia computer.Kata Kunci : Media Pembelajaran